Peran Public Relation Dalam Pemulihan Citra Pada Produk Scarlett - Bagus Budi Mulyana; Akhmad Firmansyah; Mauliya Fitriani; Kharisma Rosa Delima (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
With various events that have a negative impact on Scarlett at the time of the product being boycotted because it is pro to Zionist carried out by the owner of Scarlett. This research was conducted with the aim of finding out the role of public relations in restoring the image of Scarlett products. This study uses a literature study methodology by collecting references from previous research from several researchers. The results of the research conducted show that public relations has a very important role in regulating the flow to restore Scarlett's image to the public through the media used, such as online media and print media to provide an explanation of the case, apologies to the public to regain public trust in Scarlett in order to get a good image again.